Network analysis of PTSD in college students across different areas after the COVID-19 epidemic. Issue 1 (1st January 2021) - Sun, Rui; Qi, Junjun; Huang, Jiali; Zhou, Xiao
ABSTRACT: Background : Various studies have examined the psychological 'typhoon eye' and 'ripple' effects in mental disorders following COVID-19. However, these studies only considered the disorders as entities and assessed severity, and overlooked the differences in specific symptoms of disorders. Objectives : This aim of the study is to assess the psychological typhoon eye and ripple effects at the symptom-level in posttraumatic stress disorder (PTSD), which is considered as a common psychopathology following the COVID-19 epidemic. Method : In total, 1150 undergraduates, including 271 students from the Hubei province (e.g. epidemic centre) and 879 students from other provinces, completed the self-report questionnaire. The networks were estimated and compared using the R packages. Results : Although the PTSD networks of Hubei and non-Hubei undergraduates were similarly connected and shared some symptoms with high centrality (e.g. flashbacks, irritability and anger), there were differences across the networks. Distorted cognition and no positive emotion only exhibited high centrality in the Hubei network. Physiological responses and exaggerated startle only exhibited high centrality in the non-Hubei network. Conclusion : These findings suggested that the psychological typhoon eye and ripple effects may co-exist at the symptom level. Targeted and distinct psychological services for college students in Hubei and non-Hubei provinces should be emphasized following COVID-19. HIGHLIGHTS: Irritability and anger flashbacks showed high levels of strength in both networks. Distorted cognition and no positive emotion were the most central symptoms only in the Hubei network. Physiological responses and exaggerated startle exhibited higher strength only in the non-Hubei network. There was no significant difference in global connectivity between Hubei and non-Hubei PTSD network.